Protective effects of sesamol against cisplatin-induced nephrotoxicity in rats: A mechanistic approach. (September 2020) - Singh, Thakur Gurjeet; Singh, Hardevinder Pal; Kaur, Sunpreet; Dhiman, Sonia
Abstract: Background: Acute renal failure specifically denotes tubular necrosis due to induced by ischemic injury or drugs, resulting in electrolyte imbalance along with changes in hormonal levels in renal system, causing accumulation of nitrogenous waste in the kidneys. Objective: To explore the role and mechanism of sesamol as renoprotective using cisplatin mediated nephrotoxicity in male Wistar rats. Method: In male wistar rats, a single dose of 5 mg per kg of body weight, i.p cisplatin was used to induce nephrotoxicity. Renoprotective effect of sesamol was evaluated by analyzing blood, urine, oxidative stress markers and tissue histology. Result: Present study shows that cisplatin confirms the nephrotoxicity by modifying the urinary, blood and inflammatory parameters in contrast to the vehicle control group. Sesamol at dose levels of 50 and 100 mg/kg body weight, p.o. significantly & dose dependently reverses the changes. Nephroprotective effect of sesamol was abolished by PPAR-γ inhibitor, BADGE (30 mg/kg, i.p .) in rats. Conclusion: Our study clearly indicates the nephroprotective activity of sesamol by PPAR-γ agonism against cisplatin-induced nephrotoxicity in rats. Highlights: Cisplatin has been known to induce oxidative damages and inflammatory responses in renal Tissue. Sesamol derived from sesame lignans, is known to have free radical scavenging as well as antioxidant properties. Activation of PPAR-γ triggers protection in different models of renal failure. Nephrotoxicity has been assessed in terms of altered renal function test and histopathological alterations. Sesamol mediated renoprotective effects may involve activation of PPAR-γ dependent signaling pathway.